Translational aspects of epithelioid sarcoma: current consensus - Grünewald, Thomas G. P.; Postel-Vinay, Sophie; Nakayama, Robert T.; Berlow, Noah E.; Bolzicco, Andrea; Cerullo, Vincenzo; Dermawan, Josephine K.; Frezza, Anna Maria; Italiano, Antoine; Jin, Jia Xiang; Le Loarer, Francois; Martin-Broto, Javier; et al. (Clinical cancer research, 2024)
Epithelioid sarcoma (EpS) is an ultra-rare malignant soft-tissue cancer mostly affecting adolescents and young adults. EpS often exhibits an unfavorable clinical course with fatal outcome in ∼50% of cases despite aggressive multimodal therapies combining surgery, chemotherapy, and irradiation. EpS is traditionally classified in a more common, less aggressive distal (classic) type and a rarer aggressive proximal type. Both subtypes are characterized by a loss of nuclear INI1 expression, most often following homozygous deletion of its encoding gene, SMARCB1—a core subunit of the SWI/SNF chromatin remodeling complex. In 2020, the EZH2 inhibitor tazemetostat was the first targeted therapy approved for EpS, raising new hopes. Still, the vast majority of patients did not benefit from this drug or relapsed rapidly. Further, other recent therapeutic modalities, including immunotherapy, are only effective in a fraction of patients. Thus, novel strategies, specifically targeted to EpS, are urgently needed. To accelerate translational research on EpS and eventually boost the discovery and development of new diagnostic tools and therapeutic options, a vibrant translational research community has formed in past years and held two international EpS digital expert meetings in 2021 and 2023. This review summarizes our current understanding of EpS from the translational research perspective and points to innovative research directions to address the most pressing questions in the field, as defined by expert consensus and patient advocacy groups.